An investigation of haloacetic acid occurrence in indoor and outdoor swimming pools in Beijing China. Issue 1 (March 2020) - Yao, Shan
Abstract: Swimming is one of the most popular amusement activities. In order to keep the swimmers from microbiological, the water need to be constantly disinfected. In this study, several indoor and outdoor swimming pools water and drinking water were investigated, it has found that swimming pool water has much higher HAA concentration and toxicity than the drinking water. DCAA and TCAA are the most abundant species in the indoor and outdoor swimming pool water. In the outdoor swimming pool water, TCAA concentration was higher than DCAA, while [DCAA]/[TCAA] was higher in the indoor swimming pool water.